Matemática para deficientes mentais: contribuições do paradigma de equivalência de estímulos para o desenvolvimento e avaliação de um currículo. - Rossit, Rosana Aparecida Salvador (2003)
In daily practice, we deal with several conventional systems related to math numbers, measures, time, money, etc. Among these systems, behaviors which include money handling is fundamental in many daily aspects. While people with normal development are able to count and to make little shopping in the community, even before entering school, people with mental retardation, are not able to do so at this time, and they usually show difficulties in these behavior acquisition even when taught, through traditional academic methods. The mathematical behavior is composed by several components and would be too difficult to teach all the relations between these components directly, because of its complexity and ilimitedy possibilities of combinations. Some researchers point to the efficacy of the stimulus equivalence paradigm, due to its potential in the formation of stimulus equivalence classes and the emergency of relations derived from prior training. Therefore, there is an economy of time and route due to some relations that may emerge from the directly trained relations. Based on this justification, a teaching sequence was planned by selecting specific values and relations that could help learning classes of money handling behavior. The objective was to develop and to evaluate a curriculum based in the stimulus equivalence paradigm to teach people with mental retardation to handle money. Eleven mentally retarded participated in the study, aged between 9 and 32 years old, both genders, students of an Special Education school. The stimuli used in the study were dictated words (coins numbers and values, paper money and prices), printed numbers, pictures of coins and pictures of paper money, numbers with a plus sign between them, set of coins, paper money and coins/paper money together, printed price, real coins and real paper money. Four studies were conducted to train different relations involved in the money handling behavior. The teaching procedure was conducted in a computer using the software Mestre®. After training some relations, a probe preparation session was conducted in an extinction condition, followed by symmetry test sessions, symmetry and transitivity combined tests and generalization tests with different materials, arrangements and environments. Probes were presented immediately after training and follow-up after three and six months to evaluate learning maintenance. The results showed the efficacy of the suggested computer-based curriculum and the efficacy of the used teaching procedures, due to the acquisition of the complex skills in a reduced period of time when compared with life-time and education-time. A complex and wide relation web was taught through direct training of some relations. Others advantages were identified in the utilization of computer-based procedures, such as precision, programming efficiency, automatic record of the responses, immediate production of the results and elimination of variables which could interfere in the desired teaching. Thus, the computer-based teaching optimized the teaching-learning process, increased data reliability and controlled contingencies that allowed teaching exactly what was planned.